Detecting structural heterogeneity in single-molecule localization microscopy data - Teun A.P.M. Huijben (Nature Portfolio, 2021)
Particle fusion can improve signal-to-noise ratio in single molecule localization microscopy, but is limited by structural heterogeneity. Here, the authors demonstrate an unsupervised classification method that differentiates structurally different DNA origami structures without prior knowledge.